Modelling of OBS Data Across the Vestbakken Volcanic Province - Sørensen, Asude Arslan (The University of Bergen, 2011)
A P-Wave model of a 384 km long Ocean Bottom Seismometer profile has been modelled by use of ray-tracing. The profile, Bear Island South (BIS-2008), crossses the transtensional Vestbakken Volcanic Province and the boundary between northern Atlantic oceanic crust of the Barents Sea continental platform. This study is a part of the 4th International Polar Year (IPY) international project entitled The Dynamic Continental Margin Between the Mid-Atlantic-Ridge (Mohns Ridge, Knipovich Ridge) and the Bear Island Region'. The thickness of crust varies greatly along the profile, from 7 km at the oceanic part (southwest) to approximately 32 km at the continental part (northeast). Northeastern part of the profile represents continental crust and southwestern part shows the oceanic crust. The transition from oceanic crust to continental crust occurs in a narrow zone of 30 km width. The continent ocean boundary (COB) is located in the range 190-220 km along the profile. The Hornsund and Knølegga fault zones are modelles as significant lateral variations in velocity. Master i Geovitenskap MAMN-GEOV GEOV399